The Role of Cancer Stem Cells in Drug Resistance in Gastroesophageal Junction Adenocarcinoma - Dinneen, Kate; Baird, Anne-Marie; Ryan, Ciara; Sheils, Orla (Frontiers in Molecular Biosciences, 2021)
Gastroesophageal junction adenocarcinomas (GEJA) have dramatically increased in incidence in the western world since the mid-20th century. Their prognosis is poor, and conventional anti-cancer therapies do not significantly improve survival outcomes. These tumours are comprised of a heterogenous population of both cancer stem cells (CSC) and non-CSCs, with the former playing a crucial role in tumorigenesis, metastasis and importantly drug resistance. Due to the ability of CSCs to self-replicate, their resistance to anti-cancer therapies poses a significant barrier to effective treatment of GEJA. Ongoing drug development programmes aim to target and eradicate CSCs, however their characterisation and thus identification is difficult. CSC regulation is complex, involving an array of signalling pathways, which are in turn influenced by a number of entities including epithelial mesenchymal transition (EMT), microRNAs (miRNAs), the tumour microenvironment and tissue hypoxia. Identification of CSCs commonly relies on the expression of specific cell surface markers, yet these markers vary between different malignancies and indeed are often co-expressed in non-neoplastic tissues. The development of targeted drug therapies against CSCs thus requires an understanding of disease-specific CSC markers and regulatory pathways. This review details the current knowledge regarding CSCs in GEJA, with particular emphasis on their role in drug resistance.